2020
DOI: 10.1111/rec.13242
|View full text |Cite
|
Sign up to set email alerts
|

Replanting agricultural landscapes: how well do plants survive after habitat restoration?

Abstract: Landscape-scale habitat restoration has the potential to return ecosystem functions and services and mitigate the loss of native flora and fauna. However, restoration projects rarely monitor the effectiveness of restoration efforts, such as quantifying the establishment success (survival) of the planted species. We monitored a landscape-scale revegetation program in southeastern Australia that planted 5 million plants representing 35 native species over a 4-year period (2012-2015). We assessed the restoration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 68 publications
0
12
1
Order By: Relevance
“…On average, survival of plants after the first summer (61%, all species combined) was relatively low compared with other recent studies in south‐eastern Australia (69–94%) (Jellinek et al . 2020b), but higher than some studies in south‐western Australia (53%) (Hallett et al . 2014).…”
Section: Management Implicationscontrasting
confidence: 52%
See 3 more Smart Citations
“…On average, survival of plants after the first summer (61%, all species combined) was relatively low compared with other recent studies in south‐eastern Australia (69–94%) (Jellinek et al . 2020b), but higher than some studies in south‐western Australia (53%) (Hallett et al . 2014).…”
Section: Management Implicationscontrasting
confidence: 52%
“…In comparison, Sweet Bursaria and Drooping Sheoak had low rates of survival across sites: other studies have found these species are commonly affected by grazing (Jellinek et al . 2020b).…”
Section: Management Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within Australia, habitat loss has been anthropogenically driven by a multitude of processes that has changed the landscape notably since the late 18 th century. These processes include the introduction of invasive species, anthropogenic dispersal of non-local species, redirection/removal of natural water courses, and changes in soil properties due to agricultural practices (Kingsford 2000;Woinarski et al 2015;Jellinek et al 2020;Mallen-Cooper and Zampatti 2020). An alarming proportion of extant species are threatened by habitat loss, and, consequently, have reduced population sizes and limited genetic variation on which selection can act (Saccheri et al 1998;Amos et al 2012).…”
Section: Introductionmentioning
confidence: 99%